2021
DOI: 10.1016/j.neuropsychologia.2021.107912
|View full text |Cite
|
Sign up to set email alerts
|

The distinct and overlapping brain networks supporting semantic and spatial constructive scene processing

Abstract: Scene imagery features prominently when we recall autobiographical memories, imagine the future and navigate around in the world. Consequently, in this study we sought to better understand how scene representations are supported by the brain. Processing scenes involves a variety of cognitive processes that in the real world are highly interactive. Here, however, our goal was to separate semantic and spatial constructive scene processes in order to identify the brain areas that were distinct to each process, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The finding of greater hippocampal theta modulation during scene, than face, odd-one-out discrimination, builds upon prior fMRI studies showing that scene oddity engages the hippocampus (Lee et al, 2013;Lee et al, 2008) and the literature of MEG investigations of the hippocampus (e.g., see Ruzich et al, 2019 for reviews of hippocampal recording with MEG). Notably, when intersecting our scene-related theta modulation maps, we identified a peak in hippocampal theta modulation in the comparison of scene versus face conditions, in the anteromedial hippocampus, aligning with results of fMRI studies that have observed anteromedial hippocampal activity during scene imagery (Dalton & Maguire, 2017;McCormick & Maguire, 2021;Zeidman et al, 2015) and perceptual scene discrimination (Gardette et al, 2022;Hodgetts, Voets, et al, 2017). High-resolution fMRI work suggest that this scene-selective region likely corresponds to the anteromedial subicular complex (Dalton & Maguire, 2017;Hodgetts, Voets, et al, 2017;Read et al, 2024), which is the most connected region of the hippocampus, (in part, though not exclusively, via the fornix) to an extended hippocampal system (Aggleton & Christiansen, 2015), and is known to receive spatial input from cortical areas such as caudal inferior parietal, retrosplenial and parahippocampal cortices (Aggleton & Christiansen, 2015).…”
Section: Scene Processing May Be Supported By Theta Power Modulation ...supporting
confidence: 83%
“…The finding of greater hippocampal theta modulation during scene, than face, odd-one-out discrimination, builds upon prior fMRI studies showing that scene oddity engages the hippocampus (Lee et al, 2013;Lee et al, 2008) and the literature of MEG investigations of the hippocampus (e.g., see Ruzich et al, 2019 for reviews of hippocampal recording with MEG). Notably, when intersecting our scene-related theta modulation maps, we identified a peak in hippocampal theta modulation in the comparison of scene versus face conditions, in the anteromedial hippocampus, aligning with results of fMRI studies that have observed anteromedial hippocampal activity during scene imagery (Dalton & Maguire, 2017;McCormick & Maguire, 2021;Zeidman et al, 2015) and perceptual scene discrimination (Gardette et al, 2022;Hodgetts, Voets, et al, 2017). High-resolution fMRI work suggest that this scene-selective region likely corresponds to the anteromedial subicular complex (Dalton & Maguire, 2017;Hodgetts, Voets, et al, 2017;Read et al, 2024), which is the most connected region of the hippocampus, (in part, though not exclusively, via the fornix) to an extended hippocampal system (Aggleton & Christiansen, 2015), and is known to receive spatial input from cortical areas such as caudal inferior parietal, retrosplenial and parahippocampal cortices (Aggleton & Christiansen, 2015).…”
Section: Scene Processing May Be Supported By Theta Power Modulation ...supporting
confidence: 83%
“…In summation, we hypothesize that the constructive process in the HPC fits the memory to the current spatial context to generate a first-person perspective from the item location in the allocentric space (Yang & Naya, 2020) (Figure 6). The presence of constructive process in the HPC has also been suggested by other research groups based on human imaging studies, but the previously suggested process either combines pieces of memory for remembering the past and imagining the future or combines pieces of perception for scene perception (McCormick & Maguire, 2021;Schacter, 2012;Schacter et al, 2007;Zeidman & Maguire, 2016).…”
Section: Retrieval Of First-person Perspective From Allocentric Mnemo...mentioning
confidence: 80%
“…According to them, semantics are about the object’s fitting into the global context of a scene, while syntactic relations refer to objects being at their expected location in a scene. This notion was further supported by the different neural representations of semantic and syntactic scene violations with the former producing negative deflections in the N300-N400 time window, while the latter positive deflections in the P600 2 , 3 .…”
Section: Introductionmentioning
confidence: 85%